Don't fear the reaper: distortive media effects on workers' perceptions of injury. (2nd October 2018) - Foster, Jason; Barnetson, Bob; Matsunaga-Turnbull, Jared
ABSTRACT: This study sought to determine whether newspaper reports affect workers' beliefs about workplace injury in the western Canadian province of Alberta. This issue is important because prior research has identified that Canadian newspaper reports profoundly distort the frequency and type of workplace injuries that occur as well as which workers experience them. An online survey ( n = 2000) revealed that workers' views of injury broadly conform to distorted newspaper representations and that workers' own experiences of injury do not act as a corrective. This study provides support for the proposition that distorted newspaper reporting contributes to inaccurate public perceptions of workplace injury. This, in turn, has implications for public policy around injury prevention.